Post-transplant lymphoproliferative disorder in palatine tonsils: Case report and literature review - Lima, Marcela Silva (2013)
Purpose: To emphasize the value of the otorhinolaringology examination and the tonsil biopsy in the early management of this potentially life-threatening condition. Method: A comprehensive search was performed for studies reporting Post-transplant lymphoproliferative disorder (PTLD) data on the Pubmed and Google scholar search engines. Finally, international data from 19 different studies were included in the analysis. Discussion: Post-transplant lymphoproliferative disease is a rare but life-threatening complication after solid organ transplantation. The risk for PTLD varies with the recipient age, serostatus of the donor and recipient for Epstein-Barr virus, type of the organ transplanted and intensity of the immunosuppression. In our report, the patient was a young male who had been submitted to a kidney transplant one year before the beginning of the symptoms in the tonsils. Because PTLD in tonsils is a rare condition, the diagnosis was not promptly performed. But when it was considered the risk factors and the aspect of the palatine tonsils, the biopsy was made and the treatment was quickly set allowing a good response. PTLD can be successfully treated with reduction of the immunosuppressant and administration of antiviral agents in most patients. Conclusion: PTLD presentation in tonsils is rarely describe in the literature and the knowledge of the clinical evolution, histopathological manifestations or prognosis is still limited. Thus, in post-transplant patients this diagnosis must be remembered and treated as soon as possible. Some authors recommend a routine othorrinolaringology assessment in those patients.